Funkcjonowanie ustawowego ustroju majątkowego małżeńskiego w odniesieniu do rodzinnych zakładów produkcyjnych - Dyoniak, Andrzej (Wydział Prawa i Administracji UAM, 1985)
The system of joint property reveals, apart of positive features, several vices as well. These are particularly conspicious in the aspect of managing joint property and spouses' liability for debts. Complications can appear especially in those situations when family owned producing firms are a part of joint property. If one can nevertheless adopt a possibly wide understanding of acts of ordinary management of joint property, then family owned producing firms can efficiently operate within joint property of a normally functioning family. The system enables the spouses to use profits derived from such firms already in the time of joint property existence. Only in case of the most important acts as alienation, burdening and several others the cooperation of spouses must be required. In absence of consent for management between spouses, the spouse whose rights in joined property are being injured can demand a protection provided by law. Yet the spouse devoid of appropriate qualifications or a trade license is not competent to demand a court ruling depriving the second spouse of management rights in joint property (art. 40 of Family and Guardianship Gode F.G.C.). He can only demand to have the spouse obliged to divide profits derived from running a family owned producing firm, and also in case of damage incurred by acts of the spouse, to have him redress ithe damage, on the grounds of art. 415 of Givi] Code (C.C.). If those measures prove to be not adequate, the spouse can demand, in the last resort, a judicial dissolution of matrimonial property community (art. 52 F,G.C).
Functioning of the statutory system of matrimonial property rights with reference to functioning of family producing firms